Assessment of different techniques in the removal of a bioceramic based filling material in long oval canals: A micro-CT Study / Wael Ali Alawneh - Wael Ali, Alawneh (2019)
Introduction: iRoot SP (Innovative Bioceramix, Vancouver, Canada) was introduced as a calcium silicate-based sealer used for filling of the root canal system. However, there are concerns regarding the removal of this sealer. Aim: To evaluate the efficiency of different techniques in removing gutta-percha (GP) and iRoot SP® (Innovative Bioceramix, Vancouver, Canada) in long-oval shaped canal using micro-computed tomography (micro-CT). Materials and methods: Forty-eight single-rooted mandibular premolars with single straight canals were prepared using ProTaper Next® system (Dentsply Maillefer, Switzerland) to size X3 (30/.06) and filled with gutta-percha and iRoot SP® (Innovative Bioceramix, Vancouver, Canada) using the hydraulic technique 2 mm short of the working length. The samples were randomly divided into four groups (n=12) in each group according to the root filling removal technique: Group 1 Protaper® Universal Retreatment system (Dentsply Maillefer, Switzerland), Group 2 Protaper Universal Retreatment system combined with Xylol, Group 3 Protaper Universal Retreatment system combined with Endo Success™ Retreatment Kit, ET25 tip (Acteon, England), Group 4 Protaper Universal Retreatment combined with Xylol and Endo Success™ Retreatment Kit, ET25 tip (Acteon, England). All samples were scanned before and after the removal of the root canal filling material using micro-computed tomography imaging to assess the amount of root filling materials left. Results: Results showed no statistically significant difference in the remaining root filling material between the groups (P>0.05). The apical thirds showed the highest percentage of the remaining root canal filling material compared to the middle and coronal thirds (P<0.05). There was no significant difference between the groups in all thirds of the root (P>0.05). Results showed no statistically significant difference in the ability to achieve patency between groups (P>0.05). Conclusion: No technique proved to be superior to the others in removing bio-ceramic root filling-based material. The apical third retained a significantly iv higher percentage of its filling material compared to the middle and coronal third. Bioceramic sealers are negotiable in single, straight root canal anatomy.